Implementasi Toyota Business Practices (TBP) pada Permasalahan Proses Produksi Industri Karak Rumahan - Petra Radite; Ilham Priadythama; Fakhrina Fahma (Performa: Media Ilmiah Teknik Industri, 2015)
Karak is one of food products favored by many indonesians. Demands for this traditional meals is still high especially in the rainy season, so this food is good to be developed. In some karak cottage industries especially in urban areas, their production process has advanced, but they are still unable to fulfill high demand. In this research, Toyota Business Practices (TBP) is used to identify the root cause problem and propose improvement actions for the problem. Based on TBP’s results, the problem occurs in the cutting station where there are 900 pieces of karak which are too small or large and sloping. The root cause problem identified are the lack of a standard size for karak and equipment used is still a regular knife. Accordingly, the proposed corrective action are the creation of standards karak size and design of cutting tools to increase productivity and neatness in the cutting station.